3*x+(-4)=6*x-4

Simple and best practice solution for 3*x+(-4)=6*x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3*x+(-4)=6*x-4 equation:


Simplifying
3x + (-4) = 6x + -4
3x + -4 = 6x + -4

Reorder the terms:
-4 + 3x = 6x + -4

Reorder the terms:
-4 + 3x = -4 + 6x

Add '4' to each side of the equation.
-4 + 4 + 3x = -4 + 4 + 6x

Combine like terms: -4 + 4 = 0
0 + 3x = -4 + 4 + 6x
3x = -4 + 4 + 6x

Combine like terms: -4 + 4 = 0
3x = 0 + 6x
3x = 6x

Solving
3x = 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
3x + -6x = 6x + -6x

Combine like terms: 3x + -6x = -3x
-3x = 6x + -6x

Combine like terms: 6x + -6x = 0
-3x = 0

Divide each side by '-3'.
x = 0

Simplifying
x = 0

See similar equations:

| 90=-2.5b | | 1.3+1.5=1.4 | | 4(2*x+2)=8*x+9 | | 6m-12n= | | .5x+8=1-.25x-7 | | Y=100x^2-81 | | 2a+-2=15.7 | | 55=0.2(55-10e) | | (10x-4)=12 | | 5z-14=8z+4 | | -n+7=n-9 | | x+x(2)+x+86=180 | | -2(6x-4)=8-12*x | | -6d=-8 | | 6-3x+2x^2-x^3=0 | | -x=7x+2 | | 4*x+19=-9-6x | | x+5=7x+2 | | 25-(-5)-7= | | 3x-22+65=180 | | 5=18a | | 3+x-4=7x-2 | | 2u^2+3u-20=0 | | 4*x+3=2(2x+9) | | (x-8)=x-3 | | 6+2(2-4x)=6x+2(2x-4) | | 30+40x=35 | | 55=285-10e | | 2(6x+10y)+8=0 | | 4(x-6)-10=2x | | b=11-a | | 2(x-4)-6=-6(-2x+4)-6x |

Equations solver categories